Incorporating Environmental, Social and Governance Factors into Fixed Income Investment - Inderst, Georg; Stewart, Fiona (World Bank, Washington, DC, 2018)
This research report is the result of a partnership between the World Bank Group (WBG) and Government Pension Investment Fund (GPIF) of Japan, initiated by the World Bank Group's President, Jim Yong Kim, and GPIF's Chief Investment Officer, Hiro Mizuno. The aim is for the World Bank and IFC – member of the World Bank Group focused on the private sector – and GPIF to collaborate on initiatives that promote strategies for including environmental, social and governance (ESG) criteria in investment decisions across asset classes. Ultimately, the goal is to direct more capital towards sustainable investments and leverage the private sector to achieve the scale of investment needed to meet the Sustainable Development Goals.